Pemikiran tokoh filsafat Al Farabi - Pandita, Gavra (Maliki Interdisciplinary Journal, 2024)
Al-Farabi, a Muslim philosopher from Transoxiana, now known as Uzbekistan, is recognized as the second teacher due to his dedication to compiling, collecting, and improving the translations of Aristotle’s works. His thoughts reflect a blend of the philosophies of Plato, Aristotle, and Neoplatonism, which he then integrated with Islamic ideas. Al-Farabi believed that everything in existence is inseparable from the existence of the wajibul wujud or mukmin wujud. His concept of prophecy was closely related to Abrahamic religions (heavenly religions). Additionally, he stated that political science is the study of various actions, lifestyles, character, positive attitudes, and certain moralities. Al-Farabi is also renowned for his work in political science, where he depicted an ideal state led by a wise and just philosopher-king, showing a strong influence from Plato’s works. However, Al-Farabi did not merely imitate Plato’s ideas but also integrated them with Islamic views and Aristotelian thought, creating a unique and innovative synthesis. He emphasized the importance of education and moral development in achieving an ideal life and a just society. Besides his contributions to political philosophy, Al-Farabi made significant contributions in the fields of music, mathematics, and other sciences. He wrote Kitab al-Musiqa, a treatise outlining the theory of music and its effects on the human soul. Al-Farabi believed that music has the power to influence emotions and morality, and he stressed the importance of music in education and character development. To gain a deeper understanding of Al-Farabi’s biography, it is crucial to use a literature study method that includes exploring knowledge, ideas, and findings from various relevant sources such as articles, journals, and websites. This approach helps uncover Al-Farabi’s contributions to philosophy and science, as well as his relevance in the context of Islamic thought and the modern world. Thus, this research aims to provide deeper insights into Al-Farabi’s significant role in developing a synthesis between Greek philosophy and Islamic ideas, as well as his enduring influence across various disciplines.